2017
DOI: 10.1177/1091581817697685
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical Profile of BLZ-100, a Tumor-Targeting Fluorescent Imaging Agent

Abstract: BLZ-100 is a single intravenous use, fluorescent imaging agent that labels tumor tissue to enable more complete and precise surgical resection. It is composed of a chlorotoxin peptide covalently bound to the near-infrared fluorophore indocyanine green. BLZ-100 is in clinical development for intraoperative visualization of human tumors. The nonclinical safety and pharmacokinetic (PK) profile of BLZ-100 was evaluated in mice, rats, canines, and non-human primates (NHP). Single bolus intravenous administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 29 publications
(40 reference statements)
1
29
0
Order By: Relevance
“…Studies have confirmed the specificity of CTLX binding to GBM, demonstrating its exquisite ability to distinguish between tumor and normal brain tissues . A fluorescently labeled CLTX agent is currently under clinical investigation as a tumor imaging agent to enable more precise surgical resection . When incorporated into CARs, CLTX redirects T cells for specific tumor recognition with negligible off‐target effects on normal cells or tissues .…”
Section: Overcoming Tumor Heterogeneitymentioning
confidence: 91%
See 1 more Smart Citation
“…Studies have confirmed the specificity of CTLX binding to GBM, demonstrating its exquisite ability to distinguish between tumor and normal brain tissues . A fluorescently labeled CLTX agent is currently under clinical investigation as a tumor imaging agent to enable more precise surgical resection . When incorporated into CARs, CLTX redirects T cells for specific tumor recognition with negligible off‐target effects on normal cells or tissues .…”
Section: Overcoming Tumor Heterogeneitymentioning
confidence: 91%
“…130 A fluorescently labeled CLTX agent is currently under clinical investigation as a tumor imaging agent to enable more precise surgical resection. 131,132 When incorporated into CARs, CLTX redirects T cells for specific tumor recognition with negligible off-target effects on normal cells or tissues. 129 The development of a CLTX-CAR has shown the potential for peptide binding to redirect CAR T cell cytotoxicity.…”
Section: Discovering New Targetsmentioning
confidence: 99%
“…Other promising candidates for target biomolecules for cancer imaging include the prostatespecific membrane antigen (PSMA), 57,58 cycloxygenase-2 (COX-2) 59,60 and chlorotoxin venom (CTX). 61,62 A preclinical study 63 and Phase I clinical trial of the NIR optical imaging agent for CTX have been completed, and its safety and promising results were demonstrated (NCT02496065).…”
Section: Biomedical Analysis By Optical Imagingmentioning
confidence: 99%
“…The classification of GBM subtypes has illustrated the heterogeneity across patients, and more recent studies using single cell sequencing also revealed considerable genetic variations among intratumoral of delivery vehicles to administer chemotherapy drugs as well as small interfering RNAs (siRNAs) (30,31). More recently, the potential of CLTX to deliver fluorescent signal specifically to tumors (named "Tumor Paint") has been demonstrated in preclinical models and is currently under clinical investigation (29,32,33). These studies have indicated that CLTX can be manipulated and harnessed for specific tumor targeting.…”
Section: Introductionmentioning
confidence: 99%